2003
DOI: 10.1111/j.1460-2466.2003.tb02911.x
|View full text |Cite
|
Sign up to set email alerts
|

Framing Identities: Gender, Ethnic, and National Parity in Network Announcing of the 2002 Winter Olympics

Abstract: Analysis of 53 prime-time hours of host and reporter commentary in the 2002 SaltLake City Olympics located the degree and types of gender, ethnic, and national biases hidden within the prime-time network telecasts. Not surprisingly, most of the clock time went to men, most of the top 20 most mentioned athletes were men, and most of the athlete mentions and descriptors were devoted to men. Ethnic findings showed that four fifths of all athletes mentioned and the top 20 most mentioned were White. Surprisingly, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(56 citation statements)
references
References 22 publications
1
48
0
2
Order By: Relevance
“…Indeed, studies have shown that the Olympic Games stimulate both nationalism and patriotism (e.g. Billings & Eastman, 2003; Murata et al ., 2006). Murata et al .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies have shown that the Olympic Games stimulate both nationalism and patriotism (e.g. Billings & Eastman, 2003; Murata et al ., 2006). Murata et al .…”
Section: Introductionmentioning
confidence: 99%
“…Data obtained in the Billings & Eastman (2003) study further show that more than two-thirds of the athletes mentioned in broadcast coverage of sports were white and their mentions in fact outnumber black athletes. And, when Black athletes are mentioned, these researchers found that their mentions tend to focus on what is considered to be their natural athletic abilities (i.e., moves that are quick and powerful) without much mention to their passion, commitment, and drive for their sport.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Billings & Eastman (2003), for example, found that sports reporters covering the Olympic Games ascribed the success of White athletes to their commitment and drive in their respective sports while most of the success of Black athletes was attributed to their inherent skill and athletic ability in sports.…”
Section: Sports Journalismmentioning
confidence: 99%
See 1 more Smart Citation
“…When examining the media frame of 2004 Olympic Games in Greek, Zaharospulous observed that how the 2004 Olympic Games were framed -tell[s] us about journalistic decisions, values, and practices‖ (p. 237) and also can -point to potential effects of such practices‖ (p. 237, cf. Billings and Eastman, 2003).…”
Section: Frames Communication and The Seduction Of Publicsmentioning
confidence: 99%